Implementasi Pendidikan Humanis Pada Mata Pelajaran Al-Islam Di Sekolah Menengah Pertama Muhammadiyah 09 sidayu gresik - Mufarik Erianto; Noor Amirudin; Man Arfa Ladamay (STIT Muhammadiyah Paciran, 2022)
Education can be interpreted as a teaching effort that is deliberately carried out to develop the potentials of students so that they have the provision of life for a good society. This study aims to determine the implementation of humanist education in Al-Islam subjects at SMPM 09 Sidayu Gresik. The type of research used is qualitative research, where this approach is carried out in its entirety to the research subject where the researcher is the key instrument in the study, then the results of the approach will be described in words. Because the analysis and sharpness of qualitative research is greatly affected by the strength of the words and sentences used. Collecting data in the form of observations and interviews, namely by collecting data from several sources and requiring researchers to go into the field to observe things related to space, place, actors, activities, time, events, goals. The results of the study show that